Environmental and Economic Assessment of Portable Systems: Production of Wood-Briquettes and Torrefied-Briquettes to Generate Heat and Electricity - Kamalakanta Sahoo (Fuels, 2021)
This study assessed the environmental impacts and economic feasibility of generating heat using wood-briquettes (WBs), and heat and electricity using torrefied-wood-briquettes (TWBs). WBs and TWBs were manufactured from forest residues using portable systems and delivered to either residential consumers or power plants in the United States. An integrated cradle-to-grave life-cycle assessment (LCA) and techno-economic analysis (TEA) approach was used to quantify environmental impacts and minimum-selling prices (MSPs) of heat and electricity, respectively. Results illustrated that 82% and 59% of the cradle-to-grave global warming (GW) impact of producing heat resulted from the feedstock preparation in WBs and torrefaction in TWBs, respectively. About 46–54% of total cost in the production of heat were from labor and capital costs only. The GW impact of electricity production with TWBs was dominated by the torrefaction process (48% contribution). Capital cost (50%) was a major contributor to the total cost of electricity production using TWBs. The GW impacts of producing heat were 7–37 gCO₂eq/MJ for WBs, and 14–51 gCO₂eq/MJ for TWBs, whereas producing electricity using TWBs was 146–443 gCO₂eq/kWhe. MSPs of generating heat from WBs and TWBs were €1.09–€1.73 and €1.60–€2.26/MJ, respectively, whereas the MSP of electricity from TWBs was €20–€25/kWhe. Considering carbon and pile-burn credits, MSPs of heat and electricity were reduced by 60–90% compared to the base-case.